A thermal insulation film and a preparation method thereof
By using materials such as hyperbranched polyurethane acrylate emulsions in the insulation film to form a multiple interpenetrating network structure, the existing insulation film has been solved and the problems of delamination and unstable performance in long-term use are improved, and the flame retardant of the insulation film is improved. The performance, mechanical and mechanical properties and aging resistance have been improved, and performance stability and service life are improved.
Patent Information
- Application Number
- CN202310052002.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-02-02
AI Technical Summary
In the long-term use of existing heat insulation films, delamination, extravasation of functional additives, insufficient performance stability, flame retardancy, aging resistance and mechanical and mechanical properties, and the cost of using materials is high.
Using a top-down structure, the insulation film consists of embossed release paper, the insulation layer and the adhesive backing layer. The insulation layer is composed of hyperbranched polyurethane acrylate emulsion, hollow glass microbeads, and hydrophilic silica gas Gel powder, nano ATO dispersed slurry, 1,2,2-trifluorovinyltriphenylsilane/N-vinylcarbazole/2-[3-(2H-benzotriazole-2-yl)-4 -Hydroxyphenyl]ethyl 2-methacrylate/glycidyl methacrylate copolymer and other materials are made of materials, and multiple interpenetrating network structures are formed through free radical copolymerization and curing reaction and epoxy ring opening reaction, which improves flame retardancy and mechanical properties.
It has achieved significant improvements in flame retardancy, mechanical and aging resistance of the heat insulation film, excellent performance stability, long service life, and simple process and easy to produce on a large scale.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal insulation materials, and in particular to a thermal insulation film and a preparation method thereof. Background Art
[0002] With the development of science and technology, the improvement of living standards and the introduction of the concept of "low-carbon life", people have higher and higher requirements for the performance of thermal insulation films, and the demand is gradually increasing. Thermal insulation film is a kind of thermal insulation material. Due to its excellent thermal insulation performance, easy installation and replacement, it is widely used in curtain wall glass of large buildings and window glass of cars, playing the role of thermal insulation and energy saving.
[0003] At present, most of the commercial thermal insulation films are multi-layer polyester films, which can meet the needs of short-term use, but have poor long-term durability and are more expensive when used in the construction field. In addition, the thermal insulation films on the market have more or less defects such as low strength, poor corrosion resistance, and the flame retardancy, aging resistance and thermal insulation performance need to be further improved.
[0004] In order to solve the above problems, CN109810645B discloses a heat-insulating and energy-saving polyvinyl fluoride composite film, which includes a weather-resistant layer, a heat-insulating layer, a bonding layer and a release film in sequence, wherein the weather-resistant layer includes: by weight, 70-85% of polyvinyl fluoride resin, 15-30% of plasticizer, 0.5-1.0% of ultraviolet absorber and 0.1-0.5% of light stabilizer; the heat-insulating layer includes: by weight, 70-85% of polyvinyl fluoride resin, 10-30% of (meth) acrylic resin, 2-5% of infrared shielding agent and 0.5-1% of dispersant. The heat-insulating and energy-saving polyvinyl fluoride composite film provided by the invention has good heat insulation, weather resistance and excellent mechanical properties, and is suitable for building roofs, exterior wall insulation and automobile film; however, the multilayer structure is prone to delamination and functional additive exudation during long-term use, the material performance is not stable enough, the heat insulation and thermal insulation performance needs to be further improved, and the main material polyvinyl fluoride resin used is expensive.
[0005] It can be seen that the art still needs a thermal insulation film and a preparation method thereof with good flame retardancy and mechanical properties, good aging resistance and thermal insulation properties, excellent performance stability and long service life. Summary of the invention
[0006] The main purpose of the present invention is to provide a thermal insulation film with good flame retardancy and mechanical properties, good aging resistance and heat insulation performance, excellent performance stability and long service life, and a preparation method thereof.
[0007] To achieve the above purpose, the present invention provides a thermal insulation film, which comprises, from top to bottom, an embossed release paper, a thermal insulation layer and a back adhesive layer; the thermal insulation layer is made of the following raw materials in parts by weight: 80-90 parts of hyperbranched polyurethane acrylate emulsion, 25-35 parts of hollow glass microspheres, 5-10 parts of hydrophilic silica aerogel powder, 5-8 parts of nano ATO dispersion slurry, 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methylpropene 10-20 parts of ester / glycidyl methacrylate copolymer, 5-8 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 2-4 parts of 2,4,6-trivinyl boroxine, 1-3 parts of 2,6-bis(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone, 3-5 parts of ethylene glycol dimethacrylate, 0.8-1.2 parts of initiator, 1-3 parts of dispersant, 1-2 parts of defoaming agent, and 50-60 parts of water.
[0008] Preferably, the defoamer is at least one of the aqueous defoamer Defoamer T-607, Keying KYC-713 silicone aqueous defoamer, and Digao 810 aqueous defoamer.
[0009] Preferably, the dispersant is at least one of sodium hexametaphosphate and SN5040 polycarboxylate sodium salt dispersant.
[0010] Preferably, the initiator is at least one of MC-299 water-based UV photoinitiator, IRGACURE 500UV photoinitiator, and photoinitiator 2959.
[0011] Preferably, the preparation method of the 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / glycidyl methacrylate copolymer comprises the following steps: adding 1,2,2-trifluorovinyl triphenylsilane, N-vinyl carbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate, and azobisisobutyronitrile to a high boiling point solvent, stirring and reacting at 50-65° C. in an inert gas atmosphere for 4-6 hours, then precipitating in water, washing the precipitated polymer with ethanol for 3-5 times, and finally drying in a vacuum drying oven at 85-95° C. to constant weight.
[0012] Preferably, the mass ratio of the 1,2,2-trifluorovinyltriphenylsilane, N-vinylcarbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate, azobisisobutyronitrile, and high boiling point solvent is 1:(1-2):(0.8-1.2):1:(0.04-0.06):(15-25).
[0013] Preferably, the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone; and the inert gas is any one of nitrogen, helium, neon, and argon.
[0014] Preferably, the model of the nano-ATO dispersion slurry is VK-G06C, which is provided by Xuancheng Jinghe Environmental Protection New Materials Co., Ltd.
[0015] Preferably, the product number of the hydrophilic silica aerogel powder is 1407028, and it is provided by Forsman Technology (Beijing) Co., Ltd.
[0016] Preferably, the hollow glass microspheres have a particle size of 10-300 μm and a wall thickness of 1-2 μm.
[0017] Preferably, there is no special requirement for the source of the hyperbranched polyurethane acrylate emulsion, and the hyperbranched polyurethane acrylate emulsion is prepared according to the method of Example 1 in Chinese invention patent CN113429876B.
[0018] Another object of the present invention is to provide a method for preparing the thermal insulation film, comprising the following steps:
[0019] Step S1: After mixing the raw materials of the heat insulation layer evenly, apply them on the embossed release paper with a coating thickness of 20-30 μm; then 2 Curing under UV light for 5-8 minutes, and then drying at 80-90℃ for 15-25min;
[0020] Step S2, tear off the release paper on one side of the finished double-sided adhesive tape, and laminate it with the non-textured surface of the thermal insulation layer to form a thermal insulation film.
[0021] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0022] (1) The method for preparing the thermal insulation film disclosed in the present invention has a simple process, readily available raw materials, no special equipment and harsh conditions are required, and it is easy to achieve large-scale production, and has extremely strong industrial value.
[0023] (2) The thermal insulation film disclosed in the present invention comprises, from top to bottom, an embossed release paper, a thermal insulation layer and a back adhesive layer; such a structural design makes it easy to mount and replace; the thermal insulation layer is made of the following raw materials in parts by weight: 80-90 parts of hyperbranched polyurethane acrylate emulsion, 25-35 parts of hollow glass microspheres, 5-10 parts of hydrophilic silica aerogel powder, 5-8 parts of nano ATO dispersion slurry, 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]- ... ] ethyl 2-methacrylate / methacrylate glycidyl copolymer 10-20 parts, 2,4-diamino-6-diallylamino-1,3,5-triazine 5-8 parts, 2,4,6-trivinyl cycloboroxine 2-4 parts, 2,6-bis(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraketone 1-3 parts, ethylene glycol dimethacrylate 3-5 parts, initiator 0.8-1.2 parts, dispersant 1-3 parts, defoamer 1-2 parts, water 50-60 parts. Through the mutual coordination and joint action of various raw materials, the thermal insulation film has good flame retardancy and mechanical properties, good aging resistance and thermal insulation performance, excellent performance stability and long service life.
[0024] (3) The thermal insulation film disclosed in the present invention, the raw materials containing unsaturated olefinic bonds such as hyperbranched polyurethane acrylate emulsion, 2,4-diamino-6-diallylamino-1,3,5-triazine, 2,4,6-trivinyl cycloboroxane and ethylene glycol dimethacrylate, can undergo free radical copolymerization and curing reaction under the initiation of an initiator, and the amino group on 2,4-diamino-6-diallylamino-1,3,5-triazine can also copolymerize with 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / glycidyl methacrylate to form a curing reaction. The epoxy ring-opening reaction occurs between the epoxy group on the compound and 2,6-di(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone, so that a multiple interpenetrating network structure is formed, and isoindolinone, triazine, cycloboroxine, hyperbranched polyurethane, ester, fluorinated triphenylsilane, carbazole and benzotriazole structures are simultaneously introduced into the molecular structure. These structures cooperate with each other under the multiple effects of electronic effect, steric effect and conjugated effect, and effectively improve the flame retardancy, mechanical properties and aging resistance of the formed thermal insulation film; make the film structure denser, and further improve the thermal insulation performance.
[0025] (4) The thermal insulation film disclosed in the present invention comprises hollow glass microspheres, hydrophilic silica aerogel powder and nano-ATO dispersion slurry, which cooperate with each other and work together to make the thermal insulation film have a significant thermal insulation effect while also ensuring excellent mechanical properties. DETAILED DESCRIPTION
[0026] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0027] A heat-insulating film comprises, from top to bottom, an embossed release paper, a heat-insulating layer and a back adhesive layer; the heat-insulating layer is made of the following raw materials in parts by weight: 80 parts of hyperbranched polyurethane acrylate emulsion, 25 parts of hollow glass microspheres, 5 parts of hydrophilic silica aerogel powder, 5 parts of nano ATO dispersion slurry, 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate ester / glycidyl methacrylate copolymer 10 parts, 2,4-diamino-6-diallylamino-1,3,5-triazine 5 parts, 2,4,6-trivinyl boroxine 2 parts, 2,6-bis(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone 1 part, ethylene glycol dimethacrylate 3 parts, initiator 0.8 parts, dispersant 1 part, defoamer 1 part, water 50 parts.
[0028] The defoamer is water-based defoamer Defoamer T-607; the dispersant is sodium hexametaphosphate; and the initiator is MC-299 water-based UV photoinitiator.
[0029] The preparation method of the 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / glycidyl methacrylate copolymer comprises the following steps: adding 1,2,2-trifluorovinyl triphenylsilane, N-vinyl carbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate and azobisisobutyronitrile to a high boiling point solvent, and , stirred and reacted at 50°C for 4 hours, then precipitated in water, and the precipitated polymer was washed with ethanol 3 times, and finally placed in a vacuum drying oven at 85°C to dry to constant weight; the mass ratio of 1,2,2-trifluorovinyl triphenylsilane, N-vinyl carbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate, azobisisobutyronitrile, and high boiling point solvent is 1:1:0.8:1:0.04:15; the high boiling point solvent is dimethyl sulfoxide; the inert gas is nitrogen. The M of the copolymer was determined by GPC test using US Waters 515-2410 n =19630 g / mol, M W / M n =1.285; through elemental analysis, infrared broad spectrum analysis and weight change calculation, the mass ratio of the structural units introduced by the copolymer including 1,2,2-trifluorovinyltriphenylsilane, N-vinylcarbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate and glycidyl methacrylate is 0.98:0.99:0.8:0.97.
[0030] The model of the nano ATO dispersion slurry is VK-G06C, provided by Xuancheng Jinghe Environmental Protection New Materials Co., Ltd.; the product number of the hydrophilic silica aerogel powder is 1407028, provided by Forsman Technology (Beijing) Co., Ltd.; the particle size of the hollow glass microspheres is 10 μm and the wall thickness is 1 μm; the hyperbranched polyurethane acrylate emulsion is prepared according to the method of Example 1 in Chinese invention patent CN113429876B.
[0031] A method for preparing the thermal insulation film comprises the following steps:
[0032] Step S1: After mixing the raw materials of the heat insulation layer evenly, apply them on the embossed release paper with a coating thickness of 25 μm; then 2 Cured under UV light for 5 minutes, then dried at 80°C for 15 minutes;
[0033] Step S2, tear off the release paper on one side of the finished double-sided adhesive tape, and laminate it with the non-textured surface of the thermal insulation layer to form a thermal insulation film. Example 2
[0034] A heat-insulating film comprises, from top to bottom, an embossed release paper, a heat-insulating layer and a back adhesive layer; the heat-insulating layer is made of the following raw materials in parts by weight: 83 parts of hyperbranched polyurethane acrylate emulsion, 27 parts of hollow glass microspheres, 6 parts of hydrophilic silica aerogel powder, 6 parts of nano ATO dispersion slurry, 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / methyl acrylate 12 parts of poly(ethylene glycol) glycidyl ester copolymer, 6 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 2.5 parts of 2,4,6-trivinyl boroxine, 1.5 parts of 2,6-bis(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone, 3.5 parts of ethylene glycol dimethacrylate, 0.9 parts of initiator, 1.5 parts of dispersant, 1.2 parts of defoamer, and 53 parts of water.
[0035] The defoamer is Keying KYC-713 silicone water-based defoamer; the dispersant is SN5040 polycarboxylate sodium salt dispersant; and the initiator is IRGACURE 500UV photoinitiator.
[0036] The preparation method of the 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / glycidyl methacrylate copolymer comprises the following steps: adding 1,2,2-trifluorovinyl triphenylsilane, N-vinyl carbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate and azobisisobutyronitrile to a high boiling point solvent, stirring and reacting at 55°C for 4.5 hours in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with ethanol for 4 times, and finally drying in a vacuum drying oven at 87°C to constant weight.
[0037] The mass ratio of the 1,2,2-trifluorovinyltriphenylsilane, N-vinylcarbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate, azobisisobutyronitrile, and high boiling point solvent is 1:1.2:0.9:1:0.045:17; the high boiling point solvent is N,N-dimethylformamide; and the inert gas is helium.
[0038] The model of the nano ATO dispersion slurry is VK-G06C, provided by Xuancheng Jinghe Environmental Protection New Materials Co., Ltd.; the product number of the hydrophilic silica aerogel powder is 1407028, provided by Forsman Technology (Beijing) Co., Ltd.; the particle size of the hollow glass microspheres is 100 μm and the wall thickness is 1.2 μm; the hyperbranched polyurethane acrylate emulsion is prepared according to the method of Example 1 in Chinese invention patent CN113429876B.
[0039] A method for preparing the thermal insulation film comprises the following steps:
[0040] Step S1: After mixing the raw materials of the heat insulation layer evenly, apply them on the embossed release paper with a coating thickness of 25 μm; then 2 Cured under UV light for 6 minutes, then dried at 83°C for 17 minutes;
[0041] Step S2, tear off the release paper on one side of the finished double-sided adhesive tape, and laminate it with the non-textured surface of the thermal insulation layer to form a thermal insulation film. Example 3
[0042] A heat-insulating film comprises, from top to bottom, an embossed release paper, a heat-insulating layer and a back adhesive layer; the heat-insulating layer is made of the following raw materials in parts by weight: 85 parts of hyperbranched polyurethane acrylate emulsion, 30 parts of hollow glass microspheres, 7.5 parts of hydrophilic silica aerogel powder, 6.5 parts of nano ATO dispersion slurry, 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methylpropene 15 parts of ester / glycidyl methacrylate copolymer, 6.5 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 3 parts of 2,4,6-trivinyl boroxine, 2 parts of 2,6-bis(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone, 4 parts of ethylene glycol dimethacrylate, 1 part of initiator, 2 parts of dispersant, 1.5 parts of defoaming agent, and 55 parts of water.
[0043] The defoamer is a mixture of water-based defoamer Defoamer T-607, Keying KYC-713 silicone water-based defoamer, and Digao 810 water-based defoamer in a mass ratio of 1:2:3; the dispersant is a mixture of sodium hexametaphosphate and SN5040 polycarboxylate sodium salt dispersant in a mass ratio of 3:5; the initiator is a mixture of MC-299 water-based UV photoinitiator, IRGACURE 500UV photoinitiator, and photoinitiator 2959 in a mass ratio of 1:2:1.
[0044] The preparation method of the 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / glycidyl methacrylate copolymer comprises the following steps: adding 1,2,2-trifluorovinyl triphenylsilane, N-vinyl carbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate and azobisisobutyronitrile to a high boiling point solvent, stirring and reacting at 59° C. for 5 hours in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with ethanol for 4 times, and finally drying in a vacuum drying oven at 90° C. to constant weight.
[0045] The mass ratio of the 1,2,2-trifluorovinyltriphenylsilane, N-vinylcarbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate, azobisisobutyronitrile, and high boiling point solvent is 1:1.5:1:1:0.05:20; the high boiling point solvent is N-methylpyrrolidone; and the inert gas is neon.
[0046] The model of the nano-ATO dispersion slurry is VK-G06C, provided by Xuancheng Jinghe Environmental Protection New Materials Co., Ltd.; the product number of the hydrophilic silica aerogel powder is 1407028, provided by Forsman Technology (Beijing) Co., Ltd.; the particle size of the hollow glass microspheres is 180 μm and the wall thickness is 1.5 μm; the hyperbranched polyurethane acrylate emulsion is prepared according to the method of Example 1 in Chinese invention patent CN113429876B.
[0047] A method for preparing the thermal insulation film comprises the following steps:
[0048] Step S1: After mixing the raw materials of the heat insulation layer evenly, apply them on the embossed release paper with a coating thickness of 25 μm; then 2 Cured under UV light for 6.5 minutes, then dried at 85°C for 20 minutes;
[0049] Step S2, tear off the release paper on one side of the finished double-sided adhesive tape, and laminate it with the non-textured surface of the thermal insulation layer to form a thermal insulation film. Example 4
[0050] A heat-insulating film comprises, from top to bottom, an embossed release paper, a heat-insulating layer and a back adhesive layer; the heat-insulating layer is made of the following raw materials in parts by weight: 88 parts of hyperbranched polyurethane acrylate emulsion, 33 parts of hollow glass microspheres, 9 parts of hydrophilic silica aerogel powder, 7.5 parts of nano ATO dispersion slurry, 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / methyl acrylate 18 parts of poly(ethylene glycol) glycidyl ester copolymer, 7.5 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 3.5 parts of 2,4,6-trivinyl boroxine, 2.5 parts of 2,6-bis(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone, 4.5 parts of ethylene glycol dimethacrylate, 1.1 parts of initiator, 2.5 parts of dispersant, 1.8 parts of defoamer, and 58 parts of water.
[0051] The defoaming agent is Digo 810 water-based defoaming agent; the dispersant is sodium hexametaphosphate; and the initiator is photoinitiator 2959.
[0052] The preparation method of the 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / glycidyl methacrylate copolymer comprises the following steps: adding 1,2,2-trifluorovinyl triphenylsilane, N-vinyl carbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate and azobisisobutyronitrile to a high boiling point solvent, stirring and reacting at 63°C in an inert gas atmosphere for 5.5 hours, then precipitating in water, washing the precipitated polymer with ethanol for 5 times, and finally drying in a vacuum drying oven at 93°C to constant weight.
[0053] The mass ratio of the 1,2,2-trifluorovinyltriphenylsilane, N-vinylcarbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate, azobisisobutyronitrile, and high boiling point solvent is 1:1.8:1.1:1:0.055:23; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is argon.
[0054] The model of the nano ATO dispersion slurry is VK-G06C, provided by Xuancheng Jinghe Environmental Protection New Materials Co., Ltd.; the product number of the hydrophilic silica aerogel powder is 1407028, provided by Forsman Technology (Beijing) Co., Ltd.; the particle size of the hollow glass microspheres is 270 μm and the wall thickness is 1.8 μm; the hyperbranched polyurethane acrylate emulsion is prepared according to the method of Example 1 in Chinese invention patent CN113429876B.
[0055] A method for preparing the thermal insulation film comprises the following steps:
[0056] Step S1: After mixing the raw materials of the heat insulation layer evenly, apply them on the embossed release paper with a coating thickness of 25 μm; then 2 Cured under UV light for 7.5 minutes, then dried at 88°C for 23 minutes;
[0057] Step S2, tear off the release paper on one side of the finished double-sided adhesive tape, and laminate it with the non-textured surface of the thermal insulation layer to form a thermal insulation film. Example 5
[0058] A heat-insulating film comprises, from top to bottom, an embossed release paper, a heat-insulating layer and a back adhesive layer; the heat-insulating layer is made of the following raw materials in parts by weight: 90 parts of hyperbranched polyurethane acrylate emulsion, 35 parts of hollow glass microspheres, 10 parts of hydrophilic silica aerogel powder, 8 parts of nano ATO dispersion slurry, 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methylpropene 20 parts of ester / glycidyl methacrylate copolymer, 8 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 4 parts of 2,4,6-trivinyl boroxine, 3 parts of 2,6-bis(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone, 5 parts of ethylene glycol dimethacrylate, 1.2 parts of initiator, 3 parts of dispersant, 2 parts of defoamer, and 60 parts of water.
[0059] The defoamer is Keying KYC-713 silicone water-based defoamer; the dispersant is SN5040 polycarboxylate sodium salt dispersant; and the initiator is MC-299 water-based UV photoinitiator.
[0060] The preparation method of the 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / glycidyl methacrylate copolymer comprises the following steps: adding 1,2,2-trifluorovinyl triphenylsilane, N-vinyl carbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate and azobisisobutyronitrile to a high boiling point solvent, stirring and reacting at 65°C in an inert gas atmosphere for 6 hours, then precipitating in water, washing the precipitated polymer with ethanol for 5 times, and finally drying in a vacuum drying oven at 95°C to constant weight.
[0061] The mass ratio of the 1,2,2-trifluorovinyltriphenylsilane, N-vinylcarbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate, azobisisobutyronitrile, and high boiling point solvent is 1:2:1.2:1:0.06:25; the high boiling point solvent is N-methylpyrrolidone; and the inert gas is nitrogen.
[0062] The model of the nano ATO dispersion slurry is VK-G06C, provided by Xuancheng Jinghe Environmental Protection New Materials Co., Ltd.; the product number of the hydrophilic silica aerogel powder is 1407028, provided by Forsman Technology (Beijing) Co., Ltd.; the particle size of the hollow glass microspheres is 300 μm and the wall thickness is 2 μm; the hyperbranched polyurethane acrylate emulsion is prepared according to the method of Example 1 in Chinese invention patent CN113429876B.
[0063] A method for preparing the thermal insulation film comprises the following steps:
[0064] Step S1: After mixing the raw materials of the heat insulation layer evenly, apply them on the embossed release paper with a coating thickness of 25 μm; then 2 Cured under UV light for 8 minutes, then dried at 90°C for 25 minutes;
[0065] Step S2, tear off the release paper on one side of the finished double-sided adhesive tape, and laminate it with the non-textured surface of the thermal insulation layer to form a thermal insulation film.
[0066] Comparative Example 1
[0067] A heat insulation film is substantially the same as Example 1, except that 2,4,6-trivinyl cycloboroxine and 2,6-bis(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone are not added.
[0068] Comparative Example 2
[0069] A thermal insulation film is basically the same as Example 1, except that hollow glass microspheres are used instead of hydrophilic silica aerogel powder, and 1,2,2-trifluorovinyl triphenylsilane is not added during the preparation of 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / glycidyl methacrylate copolymer.
[0070] In order to further illustrate the beneficial technical effects of the thermal insulation films made by the embodiments of the present invention, the thermal insulation films made by the embodiments 1-5 and the comparative examples 1-2 were subjected to relevant performance tests. The test results are shown in Table 1. The test method is as follows:
[0071] Thermal conductivity: Tested in accordance with GB / T 5990-2021.
[0072] Limiting oxygen index: Tested in accordance with GB / T 2406.2-2009.
[0073] Tensile strength: Tested in accordance with GB13022-91.
[0074] Heat aging resistance: Each product was placed in an 85°C hot air artificial accelerated aging box for accelerated aging for 100 hours. After cooling to room temperature, the tensile strength test was performed again with reference to GB13022-91. The retention rate of tensile strength before and after aging was calculated. The larger the value, the better the heat aging resistance.
[0075] Table 1
[0076] project Thermal conductivity Limiting oxygen index Tensile Strength Heat aging resistance unit W / m·k % MPa % Example 1 0.040 35.6 24 98.6 Example 2 0.037 36.2 28 99.1 Example 3 0.033 36.8 30 99.4 Example 4 0.030 37.8 32 99.6 Example 5 0.028 38.1 37 99.7 Comparative Example 1 0.052 32.5 19 95.3 Comparative Example 2 0.063 33.1 22 96.1
[0077] As can be seen from Table 1, the thermal insulation film disclosed in the embodiment of the present invention has better thermal insulation performance, flame retardant performance, mechanical properties and heat aging resistance than the comparative example products. The introduction of 2,4,6-trivinyl boroxine and 2,6-bis(ethylene oxide-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone, 1,2,2-trifluorovinyltriphenylsilane and silica aerogel powder is beneficial to improving the above properties.
[0078] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A thermal insulation film, characterized in that: The invention relates to a heat-insulating layer, a backing adhesive layer, and a embossed release paper. The heat-insulating layer is made of the following raw materials in parts by weight: 80-90 parts of hyperbranched polyurethane acrylate emulsion, 25-35 parts of hollow glass microspheres, 5-10 parts of hydrophilic silica aerogel powder, 5-8 parts of nano ATO dispersion slurry, 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / methacrylic acid condensate. 10-20 parts of water glyceride copolymer, 5-8 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 2-4 parts of 2,4,6-trivinyl boroxine, 1-3 parts of 2,6-bis(oxirane-2-methyl)-1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole-1,3,5,7-tetraone, 3-5 parts of ethylene glycol dimethacrylate, 0.8-1.2 parts of initiator, 1-3 parts of dispersant, 1-2 parts of defoamer, and 50-60 parts of water; The preparation method of the 1,2,2-trifluorovinyl triphenylsilane / N-vinyl carbazole / 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate / glycidyl methacrylate copolymer comprises the following steps: adding 1,2,2-trifluorovinyl triphenylsilane, N-vinyl carbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate and azobisisobutyronitrile to a high boiling point solvent, stirring and reacting at 50-65° C. in an inert gas atmosphere for 4-6 hours, and then precipitating in water. The precipitated polymer is washed with ethanol for 3-5 times and finally dried in a vacuum drying oven at 85-95°C to constant weight; the mass ratio of the 1,2,2-trifluorovinyltriphenylsilane, N-vinylcarbazole, 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, glycidyl methacrylate, azobisisobutyronitrile and high boiling point solvent is 1:(1-2):(0.8-1.2):1:(0.04-0.06):(15-25); the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.
2. The thermal insulation film according to claim 1, characterized in that: The defoamer is at least one of the aqueous defoamer Defoamer T-607, Keying KYC-713 silicone aqueous defoamer, and Digao 810 aqueous defoamer; the dispersant is at least one of the sodium hexametaphosphate and SN5040 polycarboxylate sodium salt dispersant.
3. The thermal insulation film according to claim 1, characterized in that: The initiator is at least one of MC-299 water-based UV photoinitiator, IRGACURE 500UV photoinitiator, and photoinitiator 2959.
4. The thermal insulation film according to claim 1, characterized in that: The inert gas is any one of nitrogen, helium, neon and argon.
5. The thermal insulation film according to claim 1, characterized in that: The model of the nano-ATO dispersion slurry is VK-G06C; the particle size of the hollow glass microspheres is 10-300 μm, and the wall thickness is 1-2 μm.
6. The thermal insulation film according to any one of claims 1 to 5, characterized in that: The thermal conductivity of the thermal insulation film is ≤0.040 W / m·k, and the tensile strength is ≥24 MPa.
7. A method for preparing the thermal insulation film according to any one of claims 1 to 5, characterized in that: The steps include: Step S1: After mixing the raw materials of the heat insulation layer evenly, apply them on the embossed release paper with a coating thickness of 20-30 μm; then 2 Curing under UV light for 5-8 minutes, and then drying at 80-90℃ for 15-25min; Step S2: tear off the release paper on one side of the finished double-sided adhesive tape and laminate it with the non-textured surface of the thermal insulation layer to form a thermal insulation film.
Citation Information
Patent Citations
A heat-insulating and energy-saving polyfluorinated ethylene composite membrane
CN109810645B
A water-based UV paint and its preparation method
CN113429876B
Bridge deck waterproof material and preparation method thereof
CN112646546A
Wear-resistant and aging-resistant decorative material and preparation method thereof
CN114250037A